Gift of forgiveness inspiring stories from those who have overcome the unforgivable - Schwarzenegger, Katherine (New York Pamela Dorman Books Life/Viking, 2020)
"Written with grace and understanding and based on more than twenty in-depth interviews and stories as well as personal reflections from Schwarzenegger Pratt herself, The Gift of Forgiveness is about one of the most difficult challenges in life--learning to forgive. Here, Katherine Schwarzenegger Pratt shows us what we can learn from those who have struggled with forgiveness, some still struggling, and others who have been able to forgive what might seem truly unforgivable. The book features experiences from those well-known and unknown, including Elizabeth Smart, who learned to forgive her captors; Sue Klebold, whose son, Dylan, was one of the Columbine shooters, learning empathy and how to forgive herself; Chris Williams, who forgave the drunken teenager who killed his wife and child; and of course Schwarzenegger Pratt's own challenges and path to forgiveness in her own life. All provide different journeys to forgiveness and the process--sometimes slow and thorny, sometimes almost instantaneous--by which they learned to forgive and let go. The Gift of Forgiveness is a perfect blend of personal insights, powerful quotations, and hard-won wisdom for those seeking a way to live with greater acceptance, grace, and peace"--
Elizabeth Smart -- Chris Williams -- Sarah Klein -- Polly Sheppard -- Christy Little Jones -- Immacelee Ilibagiza -- Ron Hall -- Deborah Copaken -- Nadia Bolz-Weber -- Lewis Howes -- Scarlett Lewis -- DeVon Franklin -- Mark Rozzi -- Michelle LeClair -- Sue Klebold -- Talinda Bennington -- Mark Kelly -- Iskra Lawrence -- Tanya Brown -- Adel Altamimi -- Cora Jakes Coleman -- Sebastian Marroquin.
107862
Keywords: Forgiveness; Body, Mind & Spirit -- Inspiration & Personal Growth; Self-Help -- Motivational & Inspirational; Self-Help -- Personal Growth -- Self-Esteem; Personal narratives; Self-help publications